2021
DOI: 10.5056/jnm21042
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Symptom-based Subtypes of Functional Dyspepsia for Predicting Underlying Pathophysiologic Mechanisms and Choosing Appropriate Therapeutic Agents

Abstract: Functional dyspepsia (FD) is considered to be a heterogeneous disorder with different pathophysiological mechanisms or pathogenetic factors. In addition to traditional mechanisms, novel concepts regarding pathophysiologic mechanisms of FD have been proposed. Candidates of therapeutic agents based on novel concepts have also been suggested. FD is a symptom complex and currently diagnosed by symptom-based Rome criteria. In the Rome criteria, symptom-based subtypes of FD including postprandial distress syndrome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 112 publications
0
9
0
2
Order By: Relevance
“…The human digestive tract is the largest reservoir of microbiota in the body, so it is easily affected by the microbial ecological environment. In recent years, an increasing number of studies have confirmed that dysbiosis of the gastrointestinal microbiota plays an important role in the occurrence and progression of FD ( Tziatzios et al, 2020 ; Lee, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The human digestive tract is the largest reservoir of microbiota in the body, so it is easily affected by the microbial ecological environment. In recent years, an increasing number of studies have confirmed that dysbiosis of the gastrointestinal microbiota plays an important role in the occurrence and progression of FD ( Tziatzios et al, 2020 ; Lee, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, dyspeptic symptoms are more likely to arise when multiple functional abnormalities are present ( Vanheel et al, 2017 ). There may be multiple pathophysiological mechanisms responsible for symptoms, so agents targeting only one mechanism are unlikely to be effective ( Lee, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Symptom-based subtypes, such as PDS and EPS, are believed to be more homogenous in terms of symptom-generating mechanism than the entire group of FD. 20 Recently, duodenal pathology, such as eosinophilic infiltration, has been suggested as an important mechanism for FD. 14,21 Accordingly, it is essential to determine if the conventional symptom-based subtypes could also reflect the status of the duodenal pathology.…”
Section: Discussionmentioning
confidence: 99%